Plant–pollinator interactions in apple orchards from a production and conservation perspective - Anne‐Christine Mupepele; Vivien vonKönigslöw; Anna‐Maria Bleile; Felix Fornoff; Jochen Fründ; Alexandra‐Maria Klein (Conservation Science and Practice)
Abstract In an agricultural landscape, production and conservation ideally go hand in hand. In a win‐win scenario, conservation measures, such as hedges and flower strips, provide support for biodiversity and crop production for example by increased pollination and pollinator diversity. However, these conservation measures may also decrease pollination by attracting pollinators and competing with crop flower visits. Here, we studied plant–pollinator interactions from two different perspectives. First, we looked at the production perspective investigating whether plant–pollinator networks differed between apple orchards with and without adjacent flower strips and hedges. With help of the Bayes factor, we investigated similarity and conclude that there are no differences between pollination networks with or without adjacent flower strips and hedges. Second, we looked at the conservation perspective and analyzed the impact of hedges and flower strips on pollinators and their interactions with plants before and after apple bloom in April. We showed that apple pollinators used more flower resources in flower strips and hedges across the whole season compared to isolated orchards. In orchards with flower strips and hedges, interactions were more constant over time. We conclude that flower strips and hedges are beneficial for conservation of apple pollinators without being harmful for apple flower pollination.